A clinical study of temporomandibular joint disorders -an analysis based on the Japanese subtype classification - Shibuya, Yasuyuki; Takeuchi, Junichiro; Ikehata, Noriko; Akashi, Masaya; Fujita, Tsuyoshi; Yokoo, Satoshi; Umeda, Masahiro; Komori, Takahide (Kobe journal of the medical sciences, 2007)
In this study, cases of temporomandibular joint disorder (TMJD) were analyzed based on the subtype classification established by Japanese Society for the Temporomandibular Joint (JSTMJ) in 2001. The subject of our investigation consisted of cases who visited to the department of Oral and Maxillofacial Surgery of Kobe University Hospital in 2002 because of TMJD. Among them, any cases with no physical examination or strong psychogenic factors related to their symptoms were excluded. As a result, a total of 195 cases were investigated in this study. These cases consisted of 50 males and 145 females with a mean age of 38.1 years, and they were classified as type I (28 cases), type II (7 cases), type IIIa (91 cases), type IIIb (44 cases) and type IV (25 cases). The most frequently used therapy of the all diagnostic categories was a stabilization type of splint therapy (99 cases), and medication with muscle relaxants (52 cases) or analgesics (50 cases) ranked thereafter. All cases were followed until December 2004, and the results of the treatment were classified into 5 categories of 'improved', 'effective', 'no change', 'deteriorated' and 'discontinued'. No cases with a deterioration of symptoms were observed, while 109 cases (55.9%) were assessed as either 'improved' or 'effective'.